The civil service corps in the Federal Republic of Germany and the right of remonstration as the right to refuse to carry out an official order by a state official (Discourse of Law and Administration, 2024)
The civil service corps in the Federal Republic of Germany is based on the Basic Law and some other laws: the Federal Law on Civil Servants, the Federal Law on Wages and the Law on Social Benefits for Civil Servants. A civil service corps official is obliged to be loyal to the state and to perform his duties in a reliable and competent manner. In order to limit political influence on the part of political authorities (such as a city president, minister, state or federal government), an official has the right to remonstrate, which means refusing to carry out an official order which he deems illegal. In this situation, the official notifies the senior official, and if the official order is con f irmed in writing, he is obliged to carry out the order, but is not responsible for it.
Keywords: the right to refuse to carry out an official order by an official of the Federal Republic of Germany; the right to remonstrate; the civil service corps in the Federal Republic of Germany; the employment of a civil servant; privileges and obligations of the civil service corps